2007
DOI: 10.1021/jf0633185
|View full text |Cite
|
Sign up to set email alerts
|

Grape-Seed Procyanidins Act as Antiinflammatory Agents in Endotoxin-Stimulated RAW 264.7 Macrophages by Inhibiting NFkB Signaling Pathway

Abstract: Procyanindin extract (PE) is a mixture of polyphenols, mainly procyanidins, obtained from grape seed with putative antiinflammatory activity. We evaluated the PE effect on RAW 264.7 macrophages stimulated with lipopolysaccharide plus interferon-gamma that show a rapid enhanced production of prostaglandin E2 (PGE2) and nitric oxide (NO). Our results demonstrated that PE significantly inhibited the overproduction of NO, dose and time dependently. PE caused a marked inhibition of PGE2 synthesis when administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
174
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(197 citation statements)
references
References 41 publications
16
174
1
Order By: Relevance
“…Partition coefficients measured for proanthocyanidins [51] indicate that molecules at higher polymerization degree are more likely to partition into the lipid phase, which could facilitate interaction with membrane components [52]. Interestingly, in contrast to our findings, proanthocyanidins from grape seeds that exhibited an antiinflammatory activity when co-incubated with activated RAW 264.7 macrophages failed to decrease formation of PGE 2 , when were only pre-incubated [44], suggesting peculiar activities of pistachio proanthocyanidins.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Partition coefficients measured for proanthocyanidins [51] indicate that molecules at higher polymerization degree are more likely to partition into the lipid phase, which could facilitate interaction with membrane components [52]. Interestingly, in contrast to our findings, proanthocyanidins from grape seeds that exhibited an antiinflammatory activity when co-incubated with activated RAW 264.7 macrophages failed to decrease formation of PGE 2 , when were only pre-incubated [44], suggesting peculiar activities of pistachio proanthocyanidins.…”
Section: Discussioncontrasting
confidence: 97%
“…On the other hand, consistent with our findings, no activity of daidzein in the low micromolar range was observed in the study mentioned before [39]. Anti-inflammatory effects of proanthocyanidins have been reported in rats and mice [41], in human studies [42], as well as in inflammatory cell models [43][44][45]. In our study, HPE proanthocyanidins either oligomers or polymers were found to inhibit the LPS-induced release of NO, Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our work, and in accordance with other studies (Terra et al 2007), we compared the ability of anthocyanin metabolites to inhibit NO production in macrophages using four different treatment protocols (pre-incubation with polyphenols and activation with LPS alone or LPS plus INF-c, and co-incubation with polyphenols and LPS alone or LPS plus INF-c). When macrophages were co-incubated simultaneously with the test compound and stimulus, protocatechuic acid was found to exhibit the strongest inhibition of NO secretion.…”
Section: Resultsmentioning
confidence: 53%
“…Among the polyphenols, procyanidins (a major group of proanthocyanidins) are found in numerous fruits and fruit products, in the form of polymerized (epi)catechins with varying levels of polymerization. They have been reported to show various biological activities including antioxidant, free radical-scavenging, and anti-carcinogenic activities, inhibition of platelet aggregation [2], and anti-inflammatory activity [3]. Because flavonoids (especially procyanidins) are poorly absorbed, their biological actions may be exerted mainly in the gastrointestinal tract [4], which is also the main site of action of dietary fiber.…”
Section: Introductionmentioning
confidence: 99%